Potential of entomopathogenic fungi for the control of mealybugs (Dysmicoccus brevipes) in organic production of pineapple (Ananas comosus) - Gratereaux Báez, Wilkin V. (2009)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2009